When the Mountain Becomes a Work of Art: Arte Sella and the Transformation of an Alpine Space in Decline - Giovanni Sechi (Revue de Géographie Alpine)
Can the mise en art of a mountain area be considered a territorial resource? Can it help to boost innovation and development? How does one define the process of an Alpine space’s mise en art as a territorial resource? This article will suggest answers to these questions on the basis of a case study of Arte Sella, an evolving artistic approach that has a strong bond with the Sella Valley in the north of Italy. This project shows that the mise en art of the particular Alpine space has goals that are artistic and relate to territorial transformation and even sustainable development. This particular territorial resource evolves from a coordination between actors and the art–nature symbiosis, which makes it possible to confirm and promote the qualities of the territory. The mise en art of the Sella Valley as a specific resource is part of an innovative territorial project of which the local actors’ intentionality and the involvement are a central component.